Effect of Different Purging Gases on Weld Geometry and Mechanical Properties of 304L Stainless Steel Using GTAW Technique - Taher Abani; Azaldin Alhaj Kozam; Khaled Gewa; Mohamed Saraj; Hesham Eshabani (African Journal of Advanced Pure and Applied Sciences, 2023)
Stainless steel is used in many applications due to its resistance to corrosion. When welding austenitic stainless steel, the weld seam is exposed to heat and air, which causes oxidation. Purging is an important step to obtain high quality and prevent oxidation and thus avoiding discoloration and welding under bead discontinuities. The right purging gas is essential for getting the best results. The purpose of this study is to determine how different purging gases, such as pure nitrogen, pure argon, and a mixture of 26% N2, 4% Co2, and 70% He, affect the mechanical properties of 304 L austenitic stainless steel welds, including their tensile strength, yield strength, and hardness. The results of this study show that as no significant differences in properties have been found, it may be concluded that all named gases can be used as purging gases in the welding of austenitic stainless steels.